2023
DOI: 10.3390/app13095447
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salt Reduction and the Inclusion of Seaweed (Kappaphycus alvarezii) on the Physicochemical Properties of Chicken Patties

Abstract: This study investigates the effect of salt reduction through the inclusion of seaweed (Kappaphycus alvarezii) on the physicochemical and sensory qualities of chicken patties. A control sample (1.5% salt and without seaweed) and four chicken patty formulations were used with two levels of salt (1% and 1.5%) and two levels of seaweed (2% and 4%). Adding seaweed improves water holding capacity and minimized cooking loss in reduced-salt patties. In addition, adding seaweed decreases the shrinkage of the diameter a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Table 4 shows the outcomes of pH and color analyses of restructured black goat jerky with added USPs. The pH values were significantly higher in the ST and SM groups than in the control and SS groups (p<0.05), consistent with the results reported by Pindi et al (2023) that chicken patties containing seaweed powder showed higher pH than in a control group. The increase in pH in the USP-treated groups is considered to be caused by alkaline minerals in seaweed, such as Fe, Ca, Zn, and manganese ( Widati et al., 2021 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Table 4 shows the outcomes of pH and color analyses of restructured black goat jerky with added USPs. The pH values were significantly higher in the ST and SM groups than in the control and SS groups (p<0.05), consistent with the results reported by Pindi et al (2023) that chicken patties containing seaweed powder showed higher pH than in a control group. The increase in pH in the USP-treated groups is considered to be caused by alkaline minerals in seaweed, such as Fe, Ca, Zn, and manganese ( Widati et al., 2021 ).…”
Section: Resultssupporting
confidence: 91%
“…There has been persistent research on meat products with added seaweed or physiologically active substances from seaweed, and several functional foods are still being studied ( Gullón et al, 2020 ). For example, there have been studies on functional foods such as pork sausages, reduced salt chicken patties, and beef meatballs with sodium polyphosphate replaced by seaweed ( Mohammed et al, 2022 ; Pindi et al, 2023 ; Widati et al, 2021 ). Studies in which seaweed is added to these products mostly use a powdered form of seaweed.…”
Section: Introductionmentioning
confidence: 99%
“…The consumer acceptability of seaweed samples could be higher than the control sample, probably due to the removal of the seaweed odor during the blanching process. Similarly, in the study of Pindi et al [59], the chicken patty with 1.5% salt and 4% seaweed had the highest overall acceptability, while the patty with 1% salt and 4% seaweed had significantly higher acceptability than the control sample.…”
Section: Discussionmentioning
confidence: 60%
“…Several studies on the inclusion of macroalgae in chicken diet have shown promising results. A study utilizing red macroalgae Kappaphycus alvarezii in broiler feed resulted in improved meat quality [ 13 ]. Another study showed that supplementation with the green macroalgae Ulva rigida extensively increased the villi length of the intestine and led to better absorption of nutrition in broilers [ 14 ].…”
Section: Introductionmentioning
confidence: 99%